Path integration in desert ants, Cataglyphis fortis - Müller, Martin (1988)
Foraging desert ants, Cataglyphis fortis, continually keep track of their own posotions relative to home— i.e., integrate their tortuous outbound routes and return home along straight (inbound) routes. By experimentally manipulating the ants' outbound trajectories we show that the ants solve this path integration problem not by performing a true vector summation (as a human navigator does) but by employing a computationally simple approximation. This approximation is characterized by small, but systematic, navigational errors that helped us elucidate the ant's way of computing its mean home vector.